„Archiwum Teologiczne" w latach 1836-1837, czyli u początków czasopiśmiennictwa katolickiego w Poznaniu - Lenort, Feliks (Ecclesia. Studia z Dziejów Wielkopolski, 2012)
„Archiwum Teologiczne" - the oldest Catholic journal in Poznań, appeared in the years 1836-1837 as a quarterly. It was founded and edited by Fr. Jan Nepomucen Jabczyński, a Church historian and publisher of numerous sources on the history of the archdiocese of Gniezno and Poznań. Jabczyński himself was the author of most of the articles and materials that ran in the quarterly, and he also translated some of them from German journals. The core of the journal was a section containing theological studies and source materials to the history of the archdiocese of Gniezno and Poznań. Another valuable segment included extended reviews of Polish and foreign theological literature, mainly on pastoral issues and Church history. The journal contributed to the development of religious awareness by propagating theological knowledge and transmitting information on the life of the Church. Additionally, by presenting the glorious pages of Polish history it inspired patriotism; this was an important pursuit in a situation of the loss of independence.